AESTHETIC OUTCOME AND ONCOLOGICAL SAFETY OF NIPPLE-SPARING MASTECTOMY - Viegas, Janaina Ferreira; Lichtenfels, Martina; Souza, Alessandra Borba Anton de; Vollbrecht, Betina; Laitano Neto, Francisco; Zerwes, Felipe Pereira; Frasson, Antônio Luiz (Mastology, 2019)
Background: Nipple-sparing mastectomy (NSM) has been performed for breast cancer treatment and for women at high risk. NSM provides better aesthetic outcomes; however, its oncological safety is still controversial. Objective: To evaluate the surgical complications, oncological safety and aesthetic satisfaction of breast cancer patients undergoing NSM with immediate breast reconstruction operated by the same medical team in a Breast Cancer Center in Brazil. Method: From 2004 to 2011, an aesthetic satisfaction questionnaire was administered to women undergoing NSM followed by immediate breast reconstruction 30 or 60 days after surgery. Aesthetic satisfaction, complication rates and oncological safety were analyzed. Results: Thirty-six breast cancer patients who underwent NSMs followed by immediate reconstruction answered the questionnaire. Most of them considered their results good (51%) or great (43%) and all patients will recommend NSM as a therapeutic treatment for other women with breast cancer. Only one patient presented infection and loss of the mammary implant, and recurrence rates were satisfactory (5.5%). Conclusion: Our findings showed low complication rate, oncological safety and good aesthetic outcome related to NSM with immediate reconstruction in patients from a Breast Cancer Center in Brazil. Despite the limitations of our study, we support the use of NSM with immediate reconstruction for a better aesthetic outcome with oncological safety.